Social-ecological systems and their connectivity in the East Coast District area, Mimika Regency Central Papua Province, Indonesia - Paulangan, Yunus; Arsyad Al Amin, Muh; Yonathan Lekitoo, Hanro; Barapadang, Barnabas; Tangkelayuk, Herman; Hisyam, Muhammad (Ecological Questions, 2024)
Social-Ecological System (SES) is a system that connects the human system with natural systems where humans, as an inseparable part of nature, have functional dependencies and changes. This research was conducted on the East Coast District of Mimika Regency, Central Papua Province, Indonesia. Mimika Regency is in the southern part of Papua Island, Indonesia, characterized by swamp and mangrove forest ecosystems. Mimika Regency has a mangrove ecosystem type which is influenced by tides and large rivers that empty into the sea which carry tailings disposal. The purpose of this study was to study SESs using the Drivers-Pressure-Impact-State-Responses (DPSIR) approach. The DPSIR conceptual model is one of the frameworks showing the causal relationship between environmental systems and humans Based on analysis, it is knowed that tailings disposal causes pressure on the coastal and marine resources as well as social communities in the eastern coastal area of Mimika. Significant changed can be seen in the declining quality of forest, swamp, river, mangrove, and marine ecosystems, changes in fishing ground areas, silting of rivers and estuaries, and disruption of accessibility, which impacts the social vulnerability of the community. We identified the connectivity of the SES network formed in the East Coast District area of Mimika, which was dominant and related to livelihoods, and community perceptions of government institutions and PT. Freeport Indonesia.